Sintesis Nanopartikel Titanium Dioksida (TiO2) dengan Menggunakan Ekstrak Kulit Jeruk Gunung Omeh dan Karakteristiknya - Diana Vanda Wellia; Shelvira Edelwita; Yulia Eka Putri (Jurnal Kimia Unand, 2022)
In this study, TiO2 nanoparticles were synthesized without adding extract (0% v/v) (control) and with the addition of Gunung Omeh orange peel extract with various concentration, namely 4% v/v, 10% v/v, and 20% v /v. This study aims to study the use of Gunung Omeh orange peel extract on the formation of TiO2 nanoparticles and determine its characteristics. The characteristics of the resulting nanoparticles were characterized using X-Ray Diffraction (XRD), Diffuse Reflectance Spectroscopy, Ultraviolet-Visible (DRS UV-Vis), Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX), Brunauer-Emmett-Teller (BET), Fourier Transform Infrared (FTIR), and Thermo Gravimetric and Differential Thermal Analyzer (TG-DTA). XRD results showed that the TiO2 phase formed was anatase. The optical property of TiO2 nanoparticles showed that the obtained TiO2 nanoparticles absorb in the UV region (200-400 nm). The results of SEM-EDX show that the resulting TiO2 nanoparticles are spherical. Meanwhile, the TOKJ20 sample has increased agglomeration so that the particle shape is rod-like. The EDX spectrum showes the presence of Ti and O peaks indicated the formation of TiO2. The results of BET measurement showed that the control TiO2 had a larger surface area of 66.11 m2/g compared to TiO2 using the addition of other orange peel extracts. From the results obtained, it was concluded that, in general, the addition of orange peel extract did not significantly affect the formation of TiO2 nanoparticles.